Chronic hepatitis C virus infection and subsequent HIV viral load among women with HIV initiating antiretroviral therapy. (13th March 2018) - Willis, Sarah J.; Cole, Stephen R.; Westreich, Daniel; Edmonds, Andrew; Hurt, Christopher B.; Albrecht, Svenja; Anastos, Kathryn; Augenbraun, Michael; Fischl, Margaret; French, Audrey L.; Kalapila, Aley G.; Karim, Roksana; et al.
Abstract : Objectives: One in four persons living with HIV is coinfected with hepatitis C virus (HCV). Biological and behavioral mechanisms may increase HIV viral load among coinfected persons. Therefore, we estimated the longitudinal effect of chronic HCV on HIV suppression after ART initiation among women with HIV (WWH). Design: HIV RNA was measured every 6 months among 441 WWH in the Women's Interagency HIV Study who initiated ART from 2000 to 2015. Methods: Log-binomial regression models were used to compare the proportion of study visits with detectable HIV RNA between women with and without chronic HCV. Robust sandwich variance estimators accounted for within-person correlation induced by repeated HIV RNA measurements during follow-up. We controlled for confounding and selection bias (because of loss to follow-up and death) using inverse probability-of-exposure-and-censoring weights. Results: One hundred and fourteen women (25%) had chronic HCV before ART initiation. Overall, the proportion of visits with detectable HIV RNA was similar among women with and without chronic HCV [relative risk (RR) 1.19 (95% CI 0.72, 1.95)]. Six months after ART initiation, the proportion of visits with detectable HIV RNA among women with chronic HCV was 1.88 (95% CI 1.41–2.51) times that among women without HCV, at 2 years, the ratio was 1.60 (95% CI 1.17–2.19), and by 6 years there was no difference (1.03; 95% CI 0.60–1.79). Conclusion: Chronic HCV may negatively impact early HIV viral response to ART. These findings reaffirm the need to test persons with HIV for HCV infection, and increase engagement in HIV care and access to HCV treatment among persons with HIV/HCV coinfection. Abstract : Supplemental Digital Content is available in the text